How do companies approach brand-building and sales activations? - Sigurður Guðmundsson 1992- (2020)
This thesis deals with the subject of sales activations and brand-building campaigns and what causes the differences in how companies approach them. Having the right balance between these two methods can be crucial for the long-term success of the company. If companies are too focused on sales, they can sacrifice the long-term health of the brand. And if they are too, brand-focused, they might be missing out on possible sales. To maximize the effectiveness of a marketing campaign companies, need to know how to create the right content, how to use targeting, what metrics and media channels to use and how to balance brand-building and sales activations. The research question for this thesis is, how do companies approach sales activations and brand-building campaigns? To help answer the research question, the researcher conducted four in-depth interviews with experts from the field of marketing in Iceland. During the analysis of the qualitative results, an exciting trend was identified, and the following sub research question was formed. Are companies tracking how much of their advertising budget is spent on sales activation and brand-building? To answer the sub research, question a questioner was sent out to companies. The results of the studies show that little more than half of companies are measuring how much is they spent on brand-building and sales activations. When it comes to balancing sales activation and brand-building campaigns, it seems that a lack of awareness of what the right balance is might be causing lowered effectiveness of campaigns.